Seed endophytic bacterial profiling from wheat varieties of contrasting heat sensitivity - Aswini, Krishnan; Suman, Archna; Sharma, Pushpendra; Singh, Pradeep Kumar; Gond, Shrikant; Pathak, Devashish (Frontiers in Plant Science, 2023)
Wheat yield can be limited by many biotic and abiotic factors. Heat stress at grain filling stage is a factor reducing wheat production tremendously. . The potential role of endophytic microorganisms in mitigating plant stress through various biomolecules like enzymes, growth hormones and also by improving plant nutrition, has led to more exploration of plant microbiome for such functions. Hence, we devised this study to investigate the abundance and diversity of wheat seed endophytic bacteria (WSEB) from heatS (heat susceptible, GW322) and heatT (heat tolerant, HD3298 and HD3271) varieties by culturable and unculturable approaches. The results evidenced that the culturable diversity was more in heatS variety than the heatT and Bacillus was found dominant among the 10 different bacterial genera identified. Though WSEB population was more in heatS variety, more number of isolates from heatT varieties showed tolerance to higher temperature (up to 55°C) along with PGP activities such as IAA production and nutrient acquisition. Additionally, the metagenomic analysis of seed microbiota unveiled higher bacterial diversity, with predominance of the phyla Proteobacteria covering >50% of OTUs, followed by Firmicutes and Actinobacteria. There were considerable variations in the abundance and diversity between heat sensitivity contrasting varieties, where notably more number of thermophilic bacterial OTUs were observed in the heatT samples, which could be attributed to confer tolerance against heat stress. Further, exploring the functional characteristics of culturable and unculturable microbiome would deliver more comprehensive information on improving plant growth and productivity for sustainable agriculture.